2013
DOI: 10.1111/jocn.12361
|View full text |Cite
|
Sign up to set email alerts
|

Preventing postpartum haemorrhage: active management of the third stage of labour

Abstract: There is a need to determine gaps in the clinical practices of midwives in regard to the active management of third stage of labour, to update knowledge and practices with the latest scientific evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Furthermore, the current study found that palpation of the abdomen for early detection of an atonic uterus, assessment for placenta completeness and inspecting for cervical or vaginal tears were deemed important and become harmful if not observed when performing AMTSL. Other studies found similar observation on delayed cord clamping as a component of AMTSL but mixed findings on consideration of CCT and or UM 7,19,21,22 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, the current study found that palpation of the abdomen for early detection of an atonic uterus, assessment for placenta completeness and inspecting for cervical or vaginal tears were deemed important and become harmful if not observed when performing AMTSL. Other studies found similar observation on delayed cord clamping as a component of AMTSL but mixed findings on consideration of CCT and or UM 7,19,21,22 .…”
Section: Discussionmentioning
confidence: 60%
“…Third stage of labour (TSL) is the most critical period for PPH which is defined as the time from the birth of the baby until the expulsion of the placenta and membrane. PPH can be derived from uterine atone, lesions in the birth canal, uterine rupture, retained placental tissue or bleeding disorders 7 . However, uterus to contract and retract following child birth has been the most common cause of PPH.…”
Section: Introductionmentioning
confidence: 99%
“…Augmentation of labor with synthetic oxytocin is increasingly used worldwide [ 1 4 ]. Its purpose is to avoid or treat dystocia (prolonged labor) and associated adverse outcomes, such as a negative birth experience and cesarean section on maternal request in next pregnancy [ 5 , 6 ], chorioamnionitis, operative birth and post-partum hemorrhage [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary-type, on the other hand, is that which occurs after 24 h [4] . The causes of primary postpartum hemorrhage may be uterine atony, cervicovaginal lacerations, uterine rupture, and bleeding disorders, among which the most common cause is uterine atony [3] . On the other hand, in the secondary-type of postpartum hemorrhage, the causes may be retained placental tissue, late involution of the placental insertion site, infection, and coagulation disorders [6] .…”
Section: Introductionmentioning
confidence: 99%